Testing Mechanical Properties of Silicone Gel-Filled Breast Implants and Their Degradation - Brown, Tim; Harvie, Fraser; Kluess, Daniel (Aesthetic plastic surgery, 2024)
Breast augmentation procedures using silicone implants have become increasingly popular over the past six decades. This article addresses the concerns of patients regarding implant strength by providing clinicians with valuable information in addition to video and pictorial evidence to share, fostering reassurance. The article focuses on the structural integrity and stability of breast implants, which play a critical role in their long-term performance and patient satisfaction. Specifically, it examines the industry standards outlined by the International Organization for Standardization (ISO), with a particular emphasis on ISO14607-2018, which encompasses a range of mechanical and physio-mechanical tests, including the assessment of silicone gel-fill firmness, evaluation of shell integrity, and examination of the impact of environmental conditions on implant performance. Breast implants are not static devices and are subject to aging and fatigue-based degradation. This emphasizes the need for ongoing monitoring and evaluation to ensure the long-term safety and satisfaction of patients. By providing a comprehensive examination of breast implant structure and industry standards, this article equips clinicians with the necessary knowledge to address patient concerns and foster confidence in the safety and longevity of breast augmentation procedures using silicone implants. Level of Evidence III This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .